AL-ISTIQRĀ’ AL-MA‘NAWĪ AS A METHODOLOGICAL MODEL FOR UNDERSTANDING ISLAMIC LAW - Sabaruddin; Abdul Halim Talli; Ridwan Saleh; Haris Kulle; Rustan Darwis (MADDIKA : Journal of Islamic Family Law, 2025)
This study aims to analyze the model of understanding Islamic law through the approach of al-Istiqrā’ al-Ma‘nawī and to examine its outcomes and implications for the development of contemporary Islamic law. The al-Istiqrā’ al-Ma‘nawī approach represents an inductive method that emphasizes the extraction of meaning from various partial evidences derived from the Qur’an, Hadith, and the principles of uṣūl al-fiqh, in order to formulate inclusive legal principles oriented toward the objectives of Islamic law (Maqāṣid al-Sharī‘ah). This research employs a qualitative method with a normative-philosophical approach, involving the analysis of normative texts, the perspectives of classical and contemporary scholars, and the maqāṣid framework in understanding Islamic law. The findings indicate that the al-Istiqrā’ al-Ma‘nawī approach is capable of producing a comprehensive, integrative, and contextual understanding of Islamic law. This approach does not merely focus on the textual dimension, but also takes into account the objectives of the Sharī‘ah and the social realities surrounding the application of the law. Its relevance is reflected in its ability to respond to various contemporary issues in Islamic law, such as digital transactions, public policy, and broader concerns of social welfare. Nevertheless, this approach also has limitations, particularly the potential for subjectivity and overgeneralization if not supported by a rigorous methodological framework. Therefore, al-Istiqrā’ al-Ma‘nawī can be positioned as a strategic model in the reform of ijtihād methodology to develop Islamic law that is adaptive, moderate, and oriented toward justice and public welfare.